TINJAUAN TEOLOGIS TERHADAP PELAYANAN PEREMPUAN DALAM LUKAS 81-3: THEOLOGICAL REVIEW OF WOMEN'S MINISTRY IN LUKE 81-3 - Rodenita Barus; Sri Astuti (STTII PURWOKERTO, 2021)
There are two views regarding the position of women in the church and society, namely the traditional notion that women are only housewives and career women, which means that women can take part in social and community functions. The purpose of writing this article is to expose the passage of Luke 8: 1-3 about the women who served the Lord Jesus and His entourage on the journey of preaching the gospel of the Kingdom of God. This paper uses a literature research and hermeneutical approach. Literally, the writer concludes that the phrase